Viewer Perceptions and Preferences for Farmweek - McKayla Brubaker; Quisto Settle; Elizabeth Gregory North (Journal of Applied Communications, 2016)
A survey was conducted to determine how frequently viewers watched Farmweek and to determine what their perceptions were through the lens of Uses and Gratifications. Farmweek is a weekly 30-minute news broadcast produced by Mississippi State University Extension Service. Respondents were asked about what audiences they believed the show appealed to, what decisions they have made based on viewing the show, and what topics they wanted to see on the show in the future. Almost 40% of respondents viewed the show weekly. They believed the show presented a positive view of the state and its residents, but responses were not strong for the program appealing to all residents. Respondents reported landscaping and gardening decisions were the most likely to have been influenced by watching the show. The highest number of respondents wanted to see home and garden tips in the future, followed by livestock and animal health practices. Viewing frequency had a statistically significant relationship with respondents’ perceptions related to appeals of the show. However, viewing frequency had fewer statistically significant relationships with the types of decisions respondents made based on viewing the show and their preference for future topics. Future research was recommended to broaden the scope of this line of research to other states and other types of media produced by Extension in the country. It was also recommended to research why nonviewers did not watch Farmweek.
Keywords: Agricultural News Program; Mass Media in Extension; Television; Uses and Gratifications Theory; Viewer Perceptions and Preferences